Deposition of oxides and oxinitrid thin films for medical grafts by method of pulsed magnetron sputtering; 10th International Conference on Modification of Materials with Particle Beams and Plasma Flows, Tomsk, 19-24 September 2010 - Pichugin V. F. Vladimir Fyodorovich; Yanovskiy V. P.; Morosova N. S.; Yermolovich I. M. (2010, 2010)
Oxides and oxinitrid thin films were synthesized by pulsed magnetron reactive sputteringdeposition technique. Optical emission spectroscopy was used to characterize magnetron plasma. Experiments were carried out at pressure in the range 0.1-0.5 Pa in either pure oxygen or nitrogen and in the mixtures with Ar. The structure and composition of the Ti-O and Ti-O-N films were investigated using X-ray diffraction (XRD). Morphology of the surface was analyzed by SEM technique. Nano-hardness, Young's modulus, elastic recovery, friction constant and electric properties of the films were investigated also